(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: Introduction: Muscle Relaxants Neuromuscular blocking drugs, or muscle relaxants, are administered to facilitate intubation, surgical operation and prevent patient movement through periods of high stimulation of the patient. Aims of study: The purpose of the present study is to evaluation of the most muscle relaxant in surgical operations and determine the reasons for choosing these muscle relaxants more widely than others choose. Methodology: There were total of anesthesiologists. The respondents were worked in different hospitals in Misurata (public and private hospitals). Questionnaires were distributed to anesthesiologists in 2022. Results: the most commonly used and common muscle relaxant in the operating room at Misurata Hospitals is Esmeron. Half of the target 50% attributed the reason for choosing a particular type of muscle relaxant drug as the first choice to both the availability and medical reason, and do not for one reason without the other. We note that the most used drug for age (0-2 years) is Esmeron followed by Scoline. Moreover, that the most reasons for using Esmeron is for its safety on the patient, while Scoline is due to the pediatric risk of myopathy not discovered well. The muscle relaxant drugs used with (2-6 years), are Esmeron, followed by Scoline, and one of the most important reasons for choosing Esmeron is its safety and availability for the patient. As for the reasons for choosing Scoline, it is because of its rapid effect and its less of histamine release. In addition, the results indicate that, in the case of patients aged (>6-15 years), the best muscle relaxant is Esmerone, followed by Scoline. The most common reasons for using Esmeron is its safety and availability, and it is the most widely used muscle relaxant. On the other hand, the reason for choosing Scoline is RSI (pediatric risk of myopathy not discovered well). In the case of patients aged (>15-40 years), Esmeron is the most widely used muscle relaxant for several reasons, the most important of which is its availability and safety for the patient. Scoline, due to its short duration and less histamine release. While with patients aged (>40-60 years or more), Esmeron is the most widely used muscle relaxant for several reasons, the most important of which is its availability and safety for the patient. There are also other medicines, which are Scoline, Cisatracurium andAtracrium. Conclusion: The researcher concludes that the majority of the target audience agreed that Esmeron would be the first choice with a percentage of 28.91, and Scholine as the second choice with a percentage of 21.88%, while Atracruim came in the last place as the third choice. While Atracruim came in the last place as the third choice.